(untitled) (Boston, 2008)
Emphasizing the principles of evolution and zoological science, this best-selling text describes the diversity of animal life and the fascinating adaptations that enable animals to inhabit so many ecological niches. Featuring high quality illustrations and photographs and an engaging narrative, "Integrated Principles of Zoology" is considered the standard by which other texts are measured. With its traditional organization and comprehensive coverage, this text is suitable for one- or two-semester introductory courses in zoology
Keywords: Zoology,Động vật học